Utilization of the Merdeka Mengajar Platform to Improve Teachers' Pedagogical Competence at Public Elementary School 2 Sarolangun - Noverma Noverma; Agus Salim; Darma Putra (Badan Penerbit STIEPARI Press, 2025)
The Merdeka Mengajar (PMM) Platform is one of the applications used as an implementation of the Merdeka Curriculum. This software offers a number of tools that can be used by educators to improve teaching standards. This research is a qualitative study using a descriptive method. This research was conducted at SDN 2 Sarolangun. The subjects of this research were the principal, teachers, and students at SDN 2 Sarolangun. The research instruments were interviews, observations, and documentation. The data analysis technique used in this study was qualitative data analysis which included data reduction, data presentation, and drawing conclusions. The results of this study are (1) the school policy in utilizing the Merdeka Mengajar Platform has been implemented but is not yet fully optimal because some teachers still experience technical obstacles and limited digital literacy. Continuous support and mentoring are needed so that this policy can maximize teachers' pedagogical competence, (2) in utilizing the Merdeka Mengajar Platform, teachers have utilized various features such as teaching modules and learning videos, but some teachers still do not consistently use them in planning and implementing learning. (3) Challenges and obstacles in utilizing the platform include limited internet connections, a lack of technological devices, and adapting to new features. (4) School efforts to overcome these obstacles include taking several steps, such as providing Wi-Fi, facilitating training, and providing guidance in using the platform.